การนำเสนอเชิงเปรียบเทียบของข้อมูลทางแสงและสมรรถนะของโคมไฟถนน - วินัย นาทะศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Each roadway luminaire has a different light distribution depending on lighting design from manufacturers. The behavior of light distribution is designed to fit types of road and the installation of luminaires. Therefore, road lighting designer needs to know the behavior of light distribution in order to select proper luminaires based on types of road and lighting conditions. The selection of roadway luminaires can be time consuming if there are a large number of luminaires. This thesis develops a computer program call "Roadway Luminaire Photometric Data and Performance" using Delphi 7 program in order to present the photometric data and performance of roadway luminaires based on IES and CIE standards. The developed program shows light distribution of each luminaire and compares luminaire performance indices. As a result, the proper luminaire can be chosen and the time for luminaire selection can be reduced. The developed program displays results in tables and graphics. Moreover, the developed program can modify luminous intensity from IES standard to CIE standard.